Strange Brew : Metaphors of Magic and Science in Rock Music. - Kennedy, Victor (Cambridge Scholars Publishing, 2013)
""Strange Brew"" is the title of a 1967 hit song from Cream's album Disraeli Gears, which featured the most psychedelic cover art ever. The song is what postmodern scholars, influenced by Fredric Jameson, would call a pastiche: its lyrics combine images of love, witchcraft, and getting stoned with a note-for-note rendition of Albert King's traditional blues song ""Oh Pretty Woman."" The song's title is a metaphor suggesting that words and music can mix to become a kind of magic potion. Strange ...